2012
DOI: 10.1029/2012ja017783
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of precipitating energetic ions/electrons associated with the wave‐particle interaction in the plasmaspheric plume

Abstract: [1] In this paper, we present characteristics of precipitating energetic ions/electrons associated with the wave-particle interaction in the plasmaspheric plume during the geomagnetic storm on July 18, 2005 with observations of the NOAA15 NOAA16, IMAGE satellites and Finnish network of search coil magnetometers. Conjugate observations of the NOAA15 satellite and the Finnish network of search coil magnetometers have demonstrated that a sharp enhancement of the precipitating ion flux is a result of ring current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 53 publications
(70 reference statements)
2
60
0
1
Order By: Relevance
“…[] and Yuan et al . [] on the basis of observations of the energetic proton and electron precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…[] and Yuan et al . [] on the basis of observations of the energetic proton and electron precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Liang et al (2014) showed simultaneous observations of EMIC waves excited in the CPS and loss of energetic protons. In the plasmapause or plasmaspheric plumes, in situ satellite observations have also shown that EMIC waves can scatter ring current protons into the loss cone (Erlandson and Ukhorskiy, 2001;Yuan et al, 2012b). However, to our knowledge, it is seldom reported that in situ satellite observation of energetic ions scattered into the loss cone during the satellite's passage from the plasma sheet into the plasmapause or plasmaspheric plumes.…”
Section: Y Xiong Et Al: Energetic Ions Into the Loss Conementioning
confidence: 88%
“…The interaction between ring current (RC) ions and EMIC waves in the plasmapause or plasmaspheric plumes can lead to the scattering of RC ions into the loss cone and precipitating into the atmosphere at subauroral latitudes (Jordanova et al, 2007;Yahnin et al, 2009;Spasojević and Fuselier, 2009;Yuan et al, 2010). As a result, the low-altitude NOAA spacecraft crossing the auroral zone from high to low latitudes firstly detects an isotropic proton flux distribution and subsequently detects a drop of the proton flux within the loss cone and still a strong flux of trapped particles at lower latitudes (the anisotropic zones) (Yahnin et al, 2006;Yuan et al, 2011Yuan et al, , 2012bYuan et al, , 2013. In the isotropic zones, the curved field line geometry in the magnetotail has been considered as a key mechanism causing the protons in the central plasma sheet (CPS) to be pitch angle scattered into the loss cone and subsequently precipitate in the ionosphere (e.g., Sergeev et al, 1983;Buchner and Zelenyi, 1986;Ashour-Abdalla et al, 1990;Liang et al, 2013).…”
Section: Y Xiong Et Al: Energetic Ions Into the Loss Conementioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , within the anisotropic zone, the NOAA 16 observed enhancements of precipitating RC ion/electron flux in the plasmaspheric plume. In addition, the peak of precipitating RC electron flux is equatorward to that of precipitating RC proton flux, which is in accordance with previous observations of precipitating RC ion/electron flux in the plasmaspheric plume [ Yahnin et al ., ; Yahnin and Yahnina , ; Yuan et al ., ]. Since other satellites or ground‐based magnetometers did not perform the conjugate observations with NOAA 16 during the RC ion precipitation shown in Figure , we could not obtain the data of EMIC waves.…”
Section: Discussionmentioning
confidence: 99%